The Concept and Model of Strategic Leadership and Its Importance in Increasing School Achievement (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2018)
Strategic leadership is one of the leaderships practiced by school organizations today. Organizational capabilities and individual characteristics are two key components of strategic leadership that are indispensable to ensure that this strategic leadership can be realized effectively in schools. This article discusses the concept of strategic leadership, domain and elements and theories related to strategic leadership. In addition, this study also attempts to highlight Davies and Davies 2004 strategic leadership model which has nine elements under two key components of strategic leadership i.e. organizational capability and individual characteristics. Furthermore, the final part of the study discusses the importance of strategic leadership in the school organization. An overview of previous studies also shows that strategic leadership has significant relationships with school achievement. Hence, through the practice of strategic leadership that is preached in schools, the line of leadership of the school will be more capable in helping to improve the achievement of their respective schools.